Clinical presentation of Cysticercosis in Bihar - Sunita Kumari, Priyanka, Prof. U.P Sinha, Sunil Kumar, (International Journal of Innovative Research in Medical Science, 2017)
Purpose: To study the clinical presentation and treatment outcome of patients with ocular & extracocular cysticercosis in Bihar. Method: The study included 14 patients who were diagnosed as ocular or extraocular cysticercosis presenting to Eye OPD. PMCH between January 2016 to March 2017. The mode of presentation, the results of various investigations and the treatment outcome of these cases were studied. Result: The age of the patients were between 11 to 45 years. Two patients presented with subconjunctival F.B sensation and watering. Out of eight patients with NCC, three patients presented with Seizures, headache with vomiting and two with decreased vision while, two patients presented with complain of severe headache. One patient was asymptomatic and diagnosed with positive CT scan during routine examination for occasional headaches. Three patients with intraventricular cyst presented with floaters and diminished vision. One patient presented with proptosis. CT scan was normal in cases with subconjunctival cyst. In all other patients with intravitreal cysts, orbital cyst and seven patients of NCC, CT scan was positive for cysts. In one patient with papilledema, CT was normal, hence MRI was done that showed vesicular lesions. Two patients with subconjunctival cyst and three with intraventicular cyst underwent surgery for cyst removal. Rest patients were treated with Albendazole and Prednisolone. Patients with seizures were initially treated with anticonvulsants and mannitol. Three patients with optic atrophy did not improve. No Sign of improvement of vision was seen in patients with intravitreal cyst. Rest of the patients showed improvement with treatment. Conclusion: - USG Bscan, CT scan, MRI and excisional biopsy of the cyst helps to establish the diagnosis of cysticercosis affecting eyes and brain.